Da estrada à ferrovia: o legado do Terceiro Batalhão Rodoviário em Vacaria/RS - Castilhos, Pâmela Brochetto de (My University, 2022)
In the middle of the 20th century, Brazil went through a process of integration through the construction of railways and highways. In the south of the country, this transport policy made the Campos de Cima de Serra region receive investments that materialized in the activities of the Third Road Battalion - 3rd BRv, an institution linked to the Brazilian Army. These undertakings substantially modified the social and economic coexistence of Vacaria, the city that hosted the Battalion responsible for the construction of the highway that linked the southern states. The present research aims to analyze the presence of the 3rd BRv and how the region was impacted by these works. The "sapador", the chief engineer, the nurse, the person responsible for the army market, civilian or military, assume an important role in the implementation of highways and railways in the southern region, at different times, impacting the social relations where they were established. This kind of undertaking has a duration established by the pace of the work and, when the activities are over, these workers move to other places, leaving marks of their presence. It is about this History that the research is concerned, it seeks to give visibility to the presence of the 3rd BRv through sparse documentation in the hands of the heirs of this process. In addition to this documentation, as there are still people related to the 3rd BRv, Oral History as a methodology was activated to recall the memories of that period. This narrative was produced, based on empirical and oral research, generated a documentary about the history of the presence of the 3rd BRv in Vacaria with the objective of serving as a repository to the teaching of History in the region, area of concentration of the Postgraduate Program in History at UCS. [resumo fornecido pelo autor]
Em meados do século XX, o Brasil passou por um processo de integração via construção de ferrovias e rodovias. No sul do país, essa política de transporte fez com que a região dos Campos de Cima de Serra recebesse investimentos que se materializaram nas atividades do Terceiro Batalhão Rodoviário - 3.º BRv, instituição ligada ao Exército Brasileiro. Esses empreendimentos modificaram substancialmente as convivências sociais e econômicas de Vacaria, município que acolheu o Batalhão responsável pela construção da rodovia que ligou os estados sulinos. A presente pesquisa teve como objetivo analisar a presença do 3.º BRv e como a região foi impactada com essas obras. O "sapador", o chefe de máquinas, a enfermeira, o responsável pelo mercado do exército, o civil ou militar, assumiram papel importante na implementação de rodovias e ferrovias na região sul, em diferentes momentos, impactando as relações sociais onde estiveram estabelecidas. Esse tipo de empreendimento tem uma duração estabelecida pelo ritmo das obras e, finda as atividades, esses trabalhadores se deslocam para outros lugares, deixando marcas da sua presença. É sobre essa História que a pesquisa se ocupa, ou seja, procura dar visibilidade a presença do 3.º BRv através de uma documentação esparsa nas mãos das famílias herdeiras desse processo. Para além dessa documentação, como ainda existem sujeitos relacionados ao 3.º BRv, a História Oral como metodologia foi ativada para rememorar as memórias desse período. Essa narrativa produzida, a partir da pesquisa empírica e oral, gerou um documentário sobre a história da presença do 3.º BRv em Vacaria com o objetivo de servir de repositório dessas memórias e contribuir para o ensino de História na região, área de concentração do Programa de Pós-Graduação em História da Universidade de Caxias do Sul (UCS). [resumo fornecido pelo autor]
Keywords: Vacaria (RS) - História; Ferrovias - Vacaria (RS); Rodovias - Vacaria (RS); Memória; Vacaria (Brazil) - History; Railroads - Vacaria (Brazil); Roads - Vacaria (Brazil); Memory